Decrease in articular hypoxia and synovial blood flow at early time points following infliximab and etanercept treatment in rheumatoid arthritis - Fisher, B; Donatien, P; Filer, A; Winlove, P; McInnes, I; Buckley, C; Taylor, P (Clinical and Experimental Rheumatology Sas, 2016)
Objectives: An important feature of rheumatoid arthritis (RA) is hypoxia-driven synovial angiogenesis, but the relationship between change in vascularity, as measured by power Doppler ultrasound (PDUS), and oxygen tensions is unaddressed. Methods: Metacarpophalangeal (MCP) joint PDUS was assessed in 23 patients with RA, alongside arthroscopic synovitis and oxygen tension measurements, at baseline and 4 weeks after anti-tumour necrosis factor (TNF) inhibitors. Results: Anti-TNF reduced PDUS scores, which were negatively correlated with rise in oxygen tensions. The latter was related to good EULAR response at week 52. Conclusions: Anti-TNF results in rapid reduction in synovial blood flow, with a corresponding rise in oxygen tension most marked in EULAR good responders.